2018
DOI: 10.1038/s41419-018-0431-2
|View full text |Cite
|
Sign up to set email alerts
|

miR-27a inhibits cervical adenocarcinoma progression by downregulating the TGF-βRI signaling pathway

Abstract: High-risk human papillomavirus infection is essential for the malignant transformation of cervical cancer and can inhibit host miR-27a expression. We investigated the role and mechanism of miR-27a in cervical cancer progression. miR-27a is decreased in cervical cancer cell lines and miR-27a-agomir inhibited the cell proliferation, migration, and invasion properties of HeLa (adenocarcinoma) cells, but not in SiHa cells (squamous cell carcinoma). Luciferase assays revealed that miR-27a directly targets the 3′-UT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 33 publications
1
30
0
2
Order By: Relevance
“…34,35 The results of the reporter luciferase assay suggest that several miRNAs including miR-27a, miR-142-5p, miR-153, and miR128 are direct modulators of the Nrf2. 17,18,36 On the other hand, these miRNAs have been related to human diseases such as cancer 37 and diabetes, 20 but whether these miRNAs play an active role in the pathogenesis of NAFLD remains to be determined. In the present study, we provided the evidence that among four miRNAs studied, miR-27a, miR-142-5p expression in liver cells were consistently associated with NAFLD, both in animal model and in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…34,35 The results of the reporter luciferase assay suggest that several miRNAs including miR-27a, miR-142-5p, miR-153, and miR128 are direct modulators of the Nrf2. 17,18,36 On the other hand, these miRNAs have been related to human diseases such as cancer 37 and diabetes, 20 but whether these miRNAs play an active role in the pathogenesis of NAFLD remains to be determined. In the present study, we provided the evidence that among four miRNAs studied, miR-27a, miR-142-5p expression in liver cells were consistently associated with NAFLD, both in animal model and in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…In this research we observed that treating the cells with miR-148a agomir in the absence of transfection reagent could reduce MET, ERBB3 and IGF1R gene expressions via mRNA targeting, and previous researches also described the application of agomir in mice for cancer treatment. 27,28 These results imply that co-treatment with miR-148a agomir might be a possible approach to overcome EGFR TKI resistance in NSCLC, although this idea as well as the tolerability of miR-148 agomir application need to be veried by in vivo experiments. Furthermore, to better understanding the mechanism, the effect of miR-148a on NSCLC cells with or without T790 mutations and exogenous EGFR-T790M overexpression system should be analyzed in further study.…”
Section: Discussionmentioning
confidence: 99%
“…Dysregulated miRNAs can activate or silence some oncogenes or tumour suppressors and further cause the tumorigenicity in human. As reported, differentially expressed miRNAs have contributed a lot in diverse kinds of cancers . Mechanism about the interactions between aberrantly expressed miRNAs and their targets mRNAs in cancer is under urgent priority to be revealed.…”
Section: Introductionmentioning
confidence: 97%